Луысал ке ваньзэ вераме: кылбуръёс, поэмаос / Николай Байтеряков - Байтеряков Николай Семенович (Удмуртия, 1992)
Экземпляры: Ф18 (20240227) / Инвентарный номер: 28713 / Цена: 1500.00 / Сис.шифр: С(удм) / Авт.знак: Б 18 / ГРНТИ: 17.82.10 / ББК: 84(2Рос=Удм)